Peningkatan Daya Saing dan Pendapatan UMKM melalui Pelatihan Strategi Keunggulan Bersaing pada Lapak Warga Puri Kartika Ciledug - RR Dyah Astarini; Ayu Aulia Oktaviani; Beta Oki Baliartati; Muhammad Putra; Mutia Anindita; Dewi Anggraini (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
This community service activity aims to enhance the capacity of MSME actors at Lapak Warga Puri Kartika Ciledug in developing competitive advantage strategies to strengthen their business position and increase revenue. The main challenge faced by participants is limited ability to recognize business potential, identify product uniqueness, and create value that differentiates their products from competitors. The activity involved training and mentoring focused on understanding the concept of competitive advantage, resource identification, differentiation strategies, and customer value creation. The 18 participants, mostly women, showed significant improvement in recognizing their strengths, understanding competitive strategies, and planning business development steps. This program supports developing a strategic mindset among MSME owners, shifting focus from sales to value creation and sustainable competitive advantage. Ongoing mentoring is recommended to ensure strategy implementation and continuous growth.